Effects of re-employment and prolonged unemployment on well-being, work motivation and perceived employability of young and middle aged job losers - Maslić Seršić, Darja (Array, 2013)
The demands for more intensive work flexibility and employability are often seen as the central challenge for working people today. More often than a decade ago, people make turnovers, lose their jobs, and experience periods of unemployment. It is plausible to suppose that these demands and experiences that follow them don't have the same effects on people of different age. The current study is based on proofs of negative impacts that job loss and unemployment have on individual well-being and its aim is to look further on the effects of re-employment and prolonged unemployment on young (age< 35 ; M=26 ; SD=4.5) and middle-aged (age 35+ ; M=46 ; SD=6.4) persons. A follow-up study with two waves of data-collecting (second wave after 6 months) was conducted on a convenient sample (N=274) of persons of various demographic and work characteristics who recently lost their jobs and became unemployed. Several indicators of their well-being, work motivation and perceived employability were in the focus: financial strain, core self-evaluation, social support, job valuation and job-search efficacy. The results show that younger people were more often re-employed in the follow up, but no differences were found in qualification-job fit and job satisfaction between two age groups. Middle aged persons were more often unemployed after six months. The results of 2x2x2 repeated measures ANCOVAs generally proved a negative impact of unemployment on both groups, but negative effects of unemployment were more evident among older people and positive impacts of re-employment were more evident among younger people. The necessity of age sensitive approach to the effects of job loss and unemployment on well-being and work motivation will be discussed. Two important limitations of used methodology must be taken into account while observing the results: (1) The convenient sample of unemployed persons which was not totally homogeneous in length of unemployment after job loss, as well as in duration of re-employment status ; (2) Broad age categories that were observed. The study offers new longitudinal data on the individual capacities that are related to employability of people of different ages.